O devido processo legal nas sindicâncias instauradas no âmbito do corpo de bombeiros militar do estado do Amazonas - Belota, Kathleen Souza De Oliveira (2016)
With the advent of the Federal Constitution of 1988, the rights and individual warranties were exalted, conquering space, at least in legal devices and, consequently, the whole society became thirsty for glimpsing the materialization of those rights and warranties, including the military ones, which undergo specific laws, however they should not be released of the principles that govern the Human Rights, expressed not only in the Federal Constitution as also in the Universal Declaration of the Human Rights, particularly with respect to the equality principles among all the human beings.In that sense, the Federal Constitution, in its art. 5th, LV, assures the accused and the litigants in general, in lawsuit or administrative, the right to the wide defense and to the contradictory, with all the inherent resources to it and in the same pattern it is pronounced in Art. 3rd, §9th of the Constitution of the Amazon State. The research looked for consisted in checking if, as occours in other military institutions exposed during the work, the inquiries established in the Military Fire brigade of the State of Amazon, contemplated the wide defense and the contradictory, as well as the production of the means of proofs, and if the filings flowed from the disrespect to such essential procedural presuppositions, for the simple fact that the investigator doesn’t assist to those essential requirements, or if, in fact, it is permeated by a corporatism, inclusive in what refers to the post or military graduation, disrespecting one of the basic principles of the Human Rights: the dignity of the human being. An analysis of the inquiries established in the period from june/2012 to june/2014, combined with the application of 32 questionnaires and 20 interviews with military firemen made possible to hear some of them concerning the historical construction of the institution, this perceptions and existences concerning their rights when they represented as investigated, as well as the perception and difficulties found by the investigator in the execution of the procedural rite and time. The results demonstrated that half of the inquiries didn't assist to the principle of the contradictory and wide defense; that most of the inquiries were concluded by the investigator in the established time, but the solution delivered by the judging authority was presented out of the established time, giving rise in late punishments or in delay in the same filing even in face of situations in that there weren’t indications of functional irregularity. The study revealed revealed the need to review the instruments used in the establishment and solution of inquiries.